CINOLOGICAL SUPPORT IN THE UKRAINIAN CUSTOMS - SYDOROVYCH, Olena; GUTSUL, Inna; KRIVITSKY, Victor (Scientific journal «World of Finance», 2020)
Introduction. The development of the Ukrainian economy in the global world is characterized by the speeding up of integration processes, the activation of international cooperation and the intensification of economic competition. The functioning of the state in a competitive environment requires the government to implement the system of measures. They will neutralize external and internal threats, counteract their possible consequences, stimulate the search for new means and increase the effectiveness of existing ones to ensure the security of Ukraine, protect the needs, values and economic interests of the population, regions and the whole country. Purpose of the research is to study the specificity of the activities and analyze the tasks of reforming the customs of Ukraine in modern conditions. It is important to track the effectiveness of their activities in protecting customs interests, counteraction of smuggling and illegal movements of goods across the states customs border. The priority of the cynological direction development of the customs authorities are analyzed, the problems and ways to solve are identified. Methods. A set of general scientific and special research methods are used during the investigation of the features of functioning and directions of reformation in the customs of Ukraine in general and the effectiveness of attracting cynological teams in particular. They include analysis and synthesis, generalization, statistical, graphic, tabular ones. Results. As a result of the study of the cynological priorities on the activities of the customs institutions in Ukraine, procedure for organizing and conducting special training for the dog inspectors are established in order to identify smuggling of narcotic drugs, psychotropic substances, their analogues, weapons, ammunition, tobacco products, banknotes and etc. It was offer the keeping records and monitoring the recruitment of dog training teams, collecting and analyzing information about the effectiveness of their activities. In the research there are suggestions for improving the cynological direction in the State Customs Service of Ukraine are indicated. Prospects. It is necessary to focus on assessing the effectiveness of the dog support system in Ukraine and developed countries in further scientific studies. In the subsequent study we will analyze the safety, fiscal and economic effects of attracting dog training teams during the customs control, and implementing the dog training methodology in the EU countries into the practical activities of the customs authorities of Ukraine.